Root anatomy of nine orchidaceae species - Oliveira,Virginia del Carmem (1999)
Studies on the root anatomy of nine Orchidaceae species presented a multisseriated velamen, a parenchymatous cortex and a definided endodermis, in all the studied species (Catasetum fimbriatum Lindl., Dichaea bryophila Rchb. f., Encyclia calamara(Lindl.) Pabst, Epidendrum campestre Lindl., Epidendrum secundum Jacq., Miltonia flavescens Lindl., Pleurothallis smithiana Lindl., Stanhopea lietzei (Regel) Schltr. and Vanda tricolor Lindl.) Structural characters, which could be considered root adaptations to an epiphytic habit, were also common for all species.